The Soviet Secularization Project in Central Asia: Accommodation and Institutional Legacies - Thibault, Hélène (Eurostudia, 2015)
This article investigates the effects of the Soviet social engineering project and forced secularization in Central Asia. Emphasis is placed on the ideological foundations of Marxism-Leninism, its stance on atheism, its holistic character, and its ideological exclusivity. The article details the measures taken by authorities to eradicate religious beliefs during the seventy years of Soviet rule. Taking the case of Tajikistan, it highlights the remaining influence of Soviet policies on state-religion relations by reviewing the functions and responsibilities of current regulatory institutions as well as laws and official discourses framing religious practices.